CXCR2 in Acute Lung Injury - F. M. Konrad; J. Reutershan (Mediators of Inflammation)
In pulmonary inflammation, recruitment of circulating polymorphonuclear leukocytes is essential for host defense and initiates the following specific immune response. One pathological hallmark of acute lung injury and acute respiratory distress syndrome is the uncontrolled transmigration of neutrophils into the lung interstitium and alveolar space. Thereby, the extravasation of leukocytes from the vascular system into the tissue is induced by chemokines that are released from the site of inflammation. The most relevant chemokine receptors of neutrophils are CXC chemokine receptor (CXCR) 1 and CXCR2. CXCR2 is of particular interest since several studies implicate a pivotal role of this receptor in development and promotion of numerous inflammatory disorders. CXCR2 gets activated by ELR+ chemokines, including MIP-2, KC (rodents) and IL-8 (human). Since multiple ELR+ CXC chemokines act on both receptors—CXCR1 and CXCR2—a pharmacologic agent blocking both receptors seems to be advantageous. So far, several CXCR1/2 antagonists have been developed and have been tested successfully in experimental studies. A newly designed CXCR1 and CXCR2 antagonist can be orally administered and was for the first time found efficient in humans. This review highlights the role of CXCR2 in acute lung injury and discusses its potential as a therapeutic target.